Rihlah Ilmiah dan Kitabah dalam Tradisi Intelektualisme Islam Nusantara - Yana Priyatna (Laboratorium Sosiologi Universitas Nahdlatul Ulama Indonesia Jakarta, 2020)
This article aims to explain the strategy of disseminating Islamic scholarship in the Nusantara archipelago. These strategies are described by referring to the Muslim intellectual figures or scholars involved, the Islamic scholarship developed, and the context of scientific development itself. This study uses a literature-based analysis of the historical development of Islamic scholarship from the 16th century to the 20th century. The finding of this article is that there are two main strategies carried out by Islamic scholars or intellectuals in the context of developing Islam in the archipelago, namely scholarly journey (rihlah ilmiah) and kitabah. Through these findings this article is expected to enrich the understanding of the working process and the formation of Islam Nusantara as epistemic community among Southeast Asia Muslim intellectuals, especially Indonesia, in these centuries.